Effect of pre-flaring and file size on the accuracy of two electronic apex locators (Journal of Applied Oral Science, 2012)
OBJECTIVE: This ex vivo study evaluated the effect of pre-flaring and file size on the accuracy of the Root ZX and Novapex electronic apex locators (EALs). MATERIAL AND METHODS: The actual working length (WL) was set 1 mm short of the apical foramen in the palatal root canals of 24 extracted maxillary molars. The teeth were embedded in an alginate mold, and two examiners performed the electronic measurements using #10, #15, and #20 K-files. The files were inserted into the root canals until the "0.0" or "APEX" signals were observed on the LED or display screens for the Novapex and Root ZX, respectively, retracting to the 1.0 mark. The measurements were repeated after the preflaring using the S1 and SX Pro-Taper instruments. Two measurements were performed for each condition and the means were used. Intra-class correlation coefficients (ICCs) were calculated to verify the intra- and inter-examiner agreement. The mean differences between the WL and electronic length values were analyzed by the three-way ANOVA test (p